The Impacts of Leadership and Decision-Making Styles Middle Management on the QMS Implementation and Firm Performance - Mohamad Tohari; Musa, Soebowo (Emerging Markets : Business and Management Studies Journal, 2022)
In heavy equipment and mining companies, it is important to always maintain the quality of the products and services provided to customers. Quality Management System (QMS) as a standard has a very important role in maintaining the company's business continuity. Quality management includes customer focus, leadership, people engagement, process approach, improvement, evidence-based decision making, and relationship management. Middle management leadership and decision-making styles as well as the implementation of QMS are examined in this study to see the extent of their correlation with firm performance. The research was conducted on a heavy equipment company in Indonesia with a case study of PT. United Tractors, Tbk by involving 55 middle management respondents and 310 subordinates in 55 branch offices/sites throughout Indonesia. The results of the study concluded that QMS implementation was the only construct in this study that was positively relationship to firm performance, while decision making style was negatively relationship and leadership style was not significantly relationship. In another section, it was also confirmed that leadership style was negatively relationship to decision making style, it was also found that leadership and decision-making style middle management had no relationship to QMS implementation. Leadership style middle management PT. United Tractors, Tbk is known to be more inclined to the laissez faire style compared to the transformational and transactional styles, while the decision-making style is strongly predicted to dependent style compared that avoidant, rational and spontaneous styles. Keyword: Leadership style, Decision making style, QMS implementation, Firm performance